394 2, 4-D Use and Cancer Incidence in Pesticide Applicators in the Agricultural Health Study. (11th October 2013) - Beane Freeman, E; Koutros,; Alavanja,; Zahm,; Sandler,; Hines,; Thomas,; Hoppin,; Blair,
Abstract : Objectives: 2, 4-dichlorophenoxyacetic acid (2, 4-D) is one of the most widely used herbicides in the world. It has been associated with increased risk of non-Hodgkin lymphoma (NHL) in multiple epidemiologic studies, with some evidence for association with cancer at other sites. Findings from experimental studies, however, have been largely negative with respect to NHL. Within the Agricultural Health Study (AHS), a prospective cohort of licensed pesticide applicators in the United States, we evaluated use of this herbicide and multiple cancer sites. Methods: We used Poisson regression to estimate relative risks (RR) and 95% confidence intervals for cancers that occurred from enrollment in the AHS (1993–97) through 2008. Total lifetime days of use of 2, 4-D were calculated based on information provided at enrollment and at a follow-up interview conducted 5 years later. In addition, an intensity-weighting algorithm was applied to account for factors that modify exposure. Results: Overall, 78% of the 52, 324 applicators who provided information on 2, 4-D use and who were cancer free at enrollment reported using 2, 4-D. Among this group, there were 5, 168 incident cancers. Compared to non-users, there was no association with cancer risk overall (p-trend = 0.68), NHL overall (p-trend = 0.84), or any sub-type of NHL with intensity-weighted lifetime days. Conversely, in the highest quartiles, there was an elevated risk of gastric cancer (RR = 2.3, 95% CI:1.1–5.2, p-trend = 0.03) and a suggestion of elevated risk of brain cancer (RR = 2.3, 95% CI: 0.9–5.7, p-trend = 0.31). Conclusions: The results from this prospective study showed no association between use of 2, 4-D and NHL, the cancer most often linked to this herbicide. The increased risk of gastric cancer is noteworthy but supporting data are limited. Some previous studies of brain cancer have suggested a role for pesticides, particularly herbicides; to our knowledge there is no other study specifically suggesting an association with 2, 4-D.